2003
DOI: 10.1007/s11920-003-0012-6
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric aspects of Parkinson’s disease: Recent advances

Abstract: Psychiatric disturbances are a common feature of Parkinson's disease (PD), which is a degenerative disorder defined by its characteristic movement abnormalities. Its management is optimal when PD is viewed as a neuropsychiatric disorder, because this encourages consideration of the motor deficits along with its psychiatric and cognitive aspects. This review addresses the diagnosis and treatment of the most common psychiatric disorders in PD, and provides an update of related clinical research, including studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 137 publications
1
5
0
Order By: Relevance
“…Then we excluded 217 duplicate publications. The abstracts and full reports were reviewed to eliminate articles according to the following exclusion criteria: (1) studies that did not focus on cognitive abilities, for instance some studies were focused on other aspects such as prevalence, clinical correlates and managements, (2) review articles, (3) papers that did not include patients with a diagnosis of PD, (4) the investigation of other non-motor symptoms or other neuropsychiatric symptoms that were not specified in this review, (5) non-peer reviewed articles and (6) articles which were not written in the English language. In total, 41 articles met our inclusion criteria (See figure 1 and tables 1, 2 and 3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then we excluded 217 duplicate publications. The abstracts and full reports were reviewed to eliminate articles according to the following exclusion criteria: (1) studies that did not focus on cognitive abilities, for instance some studies were focused on other aspects such as prevalence, clinical correlates and managements, (2) review articles, (3) papers that did not include patients with a diagnosis of PD, (4) the investigation of other non-motor symptoms or other neuropsychiatric symptoms that were not specified in this review, (5) non-peer reviewed articles and (6) articles which were not written in the English language. In total, 41 articles met our inclusion criteria (See figure 1 and tables 1, 2 and 3).…”
Section: Methodsmentioning
confidence: 99%
“…A recent published study reported that 89% of PD patients with dementia presented with at least one neuropsychiatric symptom [1]. These symptoms cause impairments in daily living activities equal to or more than the limitations that result from motor deficits, and may lead patients to earlier admission to residential care [2][3][4]. Neuropsychiatric symptoms also occur even in the early stages of the disease.…”
Section: Introductionmentioning
confidence: 99%
“…For example, bradykinesia and facial masking resemble the psychomotor slowing, decreased initiative, and restricted affect seen in major depression or apathy. 88 In addition, several cognitive, vegetative, and somatic symptoms of major depression are commonly seen in patients with PD who do not have depression. 89 Based on these challenging aspects of recognition of depressive symptoms in PD, provisional diagnostic criteria for depression in PD have recently been recommended.…”
Section: Depressive Disordersmentioning
confidence: 99%
“…In addition to motor abnormalities, PD is associated with cognitive and psychiatric disturbances including depression, anxiety, psychotic symptoms and sleep disturbances [ 6 ],[ 7 ]. Psychiatric co-morbidities have a negative impact on the course and management of PD patients.…”
Section: Introductionmentioning
confidence: 99%